Malnutrition in Older Veterans Preparing for Surgery: Prevalence Rates and Evaluation (Sensitivity/Specificity) of Screening and Assessment Tools (OR36-07-19). (13th June 2019) - Starr, Kathryn Porter; Young, Kenlyn; Loyack, Nancy; Lagoo-Deenadayalan, Sandhya; Heflin, Mitchell; Pieper, Carl; Bales, Connie
Abstract: Objectives: Malnourished older adults are at high risk for poor surgical outcomes, yet screening prior to surgery is not required and rarely conducted. For older adults anticipating elective surgery, there is an opportunity to detect and correct malnutrition prior to surgery. However, there is limited evidence regarding the appropriate nutrition screening and assessment tools to use in this population and the extent of nutritional risk is unknown. The purposes of this study were (1) to assess the usefulness of a nutrition screening tool (Nutritional Risk Screening-2002; NRS-2002) and a nutrition assessment tool (Patient Generated Subjective Global Assessment; PG-SGA) by determining their sensitivity and specificity compared to the Nutrition Focused Physical Exam (NFPE) and (2) use these tools to identify the prevalence of nutritional risk and malnutrition in older, high risk Veterans preparing for elective abdominal surgery. Methods: Older Veterans ( N = 76) referred to the VA Perioperative Optimization of Senior Health interdisciplinary clinic that targets high risk older patients preparing for elective surgery were administered the NRS-2002, PG-SGA and the NFPE by trained RDs. A contingency table was used to determine the sensitivity and specificity of the NRS-2002 and PG-SGA compared to the NFPE. Results: Study population was 64.5% white, 86% male, and 72.3 ± 5.9 years of age. Results of sensitivity testing showed 46.2% for the NRS-2002 and 100% for PG-SGA. Specificity was 100% for the NRS-2002 and 98% for the PG-SGA. The PG-SGA (35.5%) and NFPE (34%) identified very similar numbers of Veterans as being moderately or severely malnourished. Accordingly, the NRS-2002 identified only 15.8% of Veterans at nutritional risk. Conclusions: The most important finding is the alarming prevalence of malnutrition in this population of Veterans, more than a third were found to be malnourished. Additionally, the NRS-2002, a screening tool often used in the clinical setting, failed to identify nutritional risk in these patients, misclassifying 46.2% of malnourished patients as nourished. These results justify further work to more effectively identify and treat pronounced nutritional risk in older patients anticipating elective abdominal surgery. Funding Sources: US Department of Veterans Affairs Rehabilitation Research and Development Service Program (CDA-2/IK2 RX002348).